The Daniel K. Inouye College of Pharmacy Scripts: Improving the Accuracy of Patient Medication Lists: Performing Medication Reconciliation by Phone Prior to Appointments - Masuda, Camlyn (Hawaii J Med Public Health, 2019)
The purpose of this project was to utilize pharmacists and pharmacy students to perform comprehensive medication reconciliation by telephone prior to a patient's office visit with their primary care physician, to address any medication issues. The project's aims were to decrease polypharmacy, improve the accuracy of medication reconciliation, and to allow more time for the physician to meet with the patient. Patients were called prior to appointment and a thorough medication reconciliation was conducted including verification of current prescription medications, over-the-counter medications, and herbal supplements. A total of 21 patients were enrolled in the study, and in 36% of patients, the number of medications decreased after the intervention. However, overall, the average number of medications used by patients increased from an average of 8.9 to 9.5 medications (P = .39). All patients included in the study had at least one medication change in the electronic medical record system. Most of the changes were to add medications that were not on the medication list or to remove medications on the list that the patient was no longer taking. This study demonstrated improved accuracy with pharmacist/pharmacy student involvement in the medication reconciliation process.